ANALISIS PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DI LINGKUNGAN KECAMATAN PASAR KOTA JAMBI - Rini Yuliani (Jurnal Dinamika Manajemen, 2013)
This study is  primarily aimed at: (1) explain the effect of leadership and organizational culture on employee performance  both simultaneously and partially, and (2) determine which of the two independent variables that has   most dominant influence on the employee  performance. The results showed that leadership and organizational culture simultaneously influence  the employees performance  with cooeficent determenation R2is  54.3%. Partially, according to statistical test shows that  the  independent variables has significant influence on  the employee  performance. Furthermore, variable that has most dominant influence is leadership. Keywords: Performance Officer; leadership, and organizational culture